ENVIRONMENTAL SANITATION RELATIONSHIP WITH DIARRHEA INCIDENCE IN THE VILLAGE OF KAOFE KADATUA SUBDISTRICT BUTON COUNTY - Anwar Mbolosi (Sean Institute, 2021)
Diarrhea is a disease characterized by an increase in the frequency of bowel movements more than usual (usually this frequency more than three times per day) accompanied by changes in the shape and consistency of stool, vomiting, muntaber or usually once a day but characterized by snot or blood. Diarrheal disease is still a public health problem, some of the factors that cause diarrheal disease are caused by germs through contamination of food or drinks contaminated with feces and or direct contact with sufferers, while other factors include devotee and environmental factors. This study aims to find out the relationship of environmental sanitation with the incidence of diarrhea in the community of Kaofe Village kadatua district buton regency in 2010. This type of research is analytical survey research. The population in this study were all heads of families in Kaofe Village, the number of samples studied was 157 samples. Data collection techniques by random sampling are equipped with questionnaires to find out the relationship of environmental sanitation (provision of clean water, provision of family latrines, solid waste management, liquid waste management) with diarrheal events. The data is processed using SPSS 16.0 and presented in the form of a frequency distribution table and analysis between variables that comes with an explanation. The results showed there was a relationship of clean water supply with diarrhea incidence with a value of P = 0.000, there was a relationship of providing family latrines with diarrhea incidence with a value of P = 0.001, no relationship of solid waste management with the incidence of diarrhea P = 0.296, there was a relationship of liquid waste management with diarrhea incidence with a value of P = 0.003. Seeing the still high incidence of diarrhea in the community of Kaofe Village kadatua subdistrict, it is advisable to the community to improve environmental sanitation by improving clean water facilities, have qualified latrines, and have qualified SPAL.